THE INFLUENCE OF WORK CULTURE, WORK EXPERIENCE AND WORK LOAD ON INDRIVER DRIVERS' PERFORMANCE IN BEKASI CITY - Dewi Puspaningtyas Faeni; Muhammad Fico Firdaus (Cahaya Ilmu Bangsa, 2024)
The purpose of this study is to examine how Bekasi City's InDriver drivers' performance is impacted by work culture, experience, and workload. This study investigates the variables influencing InDriver drivers' performance utilizing the research hypothesis that workload, work culture, and experience all have an impact on employee performance—both concurrently and to some extent. The findings of this study can offer transportation service providers, like InDriver, important information about how to enhance driver wellbeing and performance. Based on the study's findings, it can be inferred that drivers can be inspired to perform better and work harder by a strong and supportive work culture. Long and diverse work experience is also acknowledged as a contributing element to The present research endeavors to examine the factors that impact the performance of InDriver drivers by applying the research hypothesis that suggests workload, work culture, and experience all have some degree of concurrent and simultaneous effects on employee performance.